Abstracts - NAA 1983 - Editorial Board, - (Nordic Archaeological Abstracts - NAA, 2021)
General, Palaeo-Mesolithic, Neolithic, Bronze Age, Celtic Iron Age, Roman Iron Age, Germanic Iron Age, Viking Age, Medieval Period, Post-Medieval - Recent, Multi-Periods/Undated